OP46 The Association Between Private Patient Status and Caesarean Delivery: A Retrospective Cohort Study of 403, 642 Childbirth Hospitalisations. (17th September 2012) - Lutomski, JE; Murphy, M; Devane, D; Meaney, S; Greene, RA
Abstract : Background: The increase in Caesarean delivery rates over the past decades has resulted in it becoming one of the most commonly performed in-hospital surgical procedures. While many Caesarean deliveries are clinically indicated, other factors, such as medico-legal fears and maternal and health professional preferences, contribute to the decision-making process. To explore non-clinical factors, we investigated differences in Caesarean delivery rates and temporal trends by private and public patient status while giving consideration to patient case-mix. Methods: A retrospective cohort study was performed on childbirth hospitalisations occurring between 2005 and 2010 in the Republic of Ireland. Procedural ICD–10-AM codes from hospital discharge records were used to identify emergency and elective Caesarean deliveries. Temporal trends in Caesarean delivery were determined using a Cochrane-Armitage test for trend. Multivariate multinomial regression analysis was used to determine the odds of Caesarean delivery (emergency or elective versus vaginal delivery) by mother's public or private status while adjusting for age, multiple gestation, previous Caesarean delivery, induction of labour, maternal morbidity and other obstetric complications. Results: 403, 642 childbirth hospitalisations reviewed; approximately one-third of women (30.2%) were booked privately. Women booked privately were more likely to be at least 30 years of age or older, married and have had a previous Caesarean delivery. Over the study period, the overall Caesarean rate increased from 22.2% to 23.8% among women booked publicly versus 30.2% to 34.7% among women booked privately (test for trend p-value <0.0001). While the emergency Caesarean rate was similar between both groups of women (14.3% versus 13.3% respectively), women booked privately were almost twice as likely to have an elective Caesarean delivery (17.8% versus 9.4%). After adjustment, women booked privately had an increased odds of both emergency (adjusted OR: 1.32; 95% CI 1.29, 1.35) and elective (adjusted OR: 1.88; 95% CI 1.83, 1.93) Caesarean delivery. Conclusion: Irrespective of obstetric risk factors, women who opted for private maternity care were significantly more likely to have a Caesarean delivery than women booked publicly. Moreover, while increasing trends in Caesarean delivery were observed among all women, the increase was disproportionately higher among women booked privately. These findings suggest that significant differences in Caesarean rates are unlikely to be explained by differences in clinical risk factors. Mixed-method research is clearly warranted to explore disparities in Caesarean delivery rates. Such research should focus on clinical decision making and the role of personal preferences of women and maternity care professionals in decisions regarding mode of birth.